Financing of School Education - Manandhar, T. B. (Administration and Management Review, 2009)
There has been a big expansion of school education system in the past few decades. The system faces several problems, mainly related to access, quality and efficiency. Several projects are being implemented to resolve the problems. Currently the government is devoting about 16% of annual budget for the education sector. Since primary education is high priority programme, about 60% of the Education Budget is allocated to this sub sector. Further about 25% of the education budget is allocated to the secondary level education. About 73% of the education budget is met by government resources, and 27% by external aid. The public schools have their own income received from fees. But the schools depend largely on government grants for major portions of their expenditure. The households/parents contribute large amount of money for education of their children even when the children attend the public schools. The local bodies (VDC, DDC, Municipality) contribute small amounts of funds for the support of the public schools. Recently, in the Three Year Interim Plan the government has made some policy commitments which have financial implications. These are: making structural changes in the school education system, and making secondary education free. These measures have to be implemented in phases in order to make financing feasible. Measures like strengthening of school management committees, and increasing the involvement of local bodies in school financing and management are required. Administration And Management Review Vol 20, No.2 August 2008 Page: 29-43